التحول الحيوي للفوسفوجيبسوم بوساطة الجراثيم المرجعة للكبريتات في أوساط تحتوي مصادر مختلفة من الكربون - ناصر, أميمة; عليا, تميم (Latakia University Journal -Basic Sciences Series, 2013)
تمت دراسة مزيج من الجراثيم المرجعة للكبريتات (Desulfotomaculum, Desulfovibro ,(Desulfotomonas من أجل التحول الحيوي للفوسفوجيبسوم المدروس. وتبين أنه يمكن إذابة الفوسفوجيبسوم (مقدرة غ/ل) في أوساط ذات مصادر مختلفة للكربون تحتوي اللاكتات (3.65/ل), كحول (2.9غ/ل), كازئين (2.8غ/ل), كانت نسبة الإذابة أقل في الوسط المحتوي الغلوكوز (2.1غ/ل), وأقل بثلاث مرات تقريباً في الوسط الذي يحتوي خلات الصوديوم (1.35/ل). تم حساب التحول الحيوي للفوسفوجيبسوم على أساس كبريت الهيدروجين المنطلق في الوسط, والذي سجل أعظم قيمة له في الوسط المزود بالكحول حيث بلغت (1.29/ل). كما وجد أن الجراثيم المعزولة فعالة جداً في إرجاع الكبريتات من الفوسفوجيبسوم في الوسط المزود بالكحول (2.15غ/ل), وتخفيض (98.03%) من الاحتياج الكيميائي للأكسجين في الوسط المزود بالغلوكوز, وأكبر كمية ذائبة للفوسفوجيبسوم أزيلت في الوسط المزود باللاكتات ثم الكحول فالكازئين كمصدر للكربون. Mixture of sulphate-reducing bacteria (SRB) (Desulfotomaculum, Desulfovibro, Desulfotomonas) were studied for the biotransformation of phosphogypsum. This study shows that the greatest reduction of phosphogypsum (g/l) was possible among different cultures of carbon containing lactate (3.65), ethanol (2.9), casein (2.8); the melting rate was lower in the medium containing glucose (2.1), and three fold less in the medium with sodium acetate(1.35) almost. The biotransformation of phosphogypsum, was calculated on the basis of amount of hydrogen sulphide in cultures. In the studied cultures the greatest amount of hydrogen sulphide was produced from medium containing alcohol (1.29g/l). These isolated bacteria were found to be very effective in the reduction of (2.15 g/l) sulfate from phosphogypsum, with (98.03 %) reduction of Chemical Oxygen Demand in medium with glucose. The greatest amount of dissolved phosphogypsum was removed from medium containing Lactate, ethanol, casein respectively as sources of carbon.